Factors promoting schistosomiasis infection in endemic rural communities of Ifedore and Ile-Oluji/Oke Igbo local government areas in Ondo State, Nigeria - Adeneye AK; Sulyman MA; Akande DO; Mafe MA (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2021)
Schistosomiasis, a chronic parasitic disease, is highly endemic in Nigeria and causes severe morbidity among school children in many poor-resource communities in the country. We investigated the factors that promote schistosomiasis infection in rural hyper-endemic communities of two LGAs in Ondo State, South West Nigeria. Data were collected through a household survey, focus group discussions, indepth interviews, key informant interviews among different categories of stakeholders in schistosomiasis control that include community adult members, school pupils, health workers and disease control officers. The quantitative and qualitative data were analysed using the Epi Info (version 6.04a) and Textbase Beta software respectively. A large number (71.1%) of respondents described schistosomiasis as a prevalent infection in their communities and 34.6% reported having a member of their households who was infected with schistosomiasis. The LGA of residence of the respondents significantly influenced the respondents' perception of the seriousness of the consequences of the disease as more respondents in Ile-Oluji/Oke Igbo LGA perceived it to be a very serious health problem than those in Ifedore LGA [27.8% Ile-Oluji/Oke Igbo LGA vs. 5.9% Ifedore LGA] (p<0.05). The results show that communities in the LGAs are endemic of schistosomiasis mainly because the people have little or no access to safe potable water thereby increasing their rate of contact with natural flowing streams, ponds and or rivers which are or may be infested with susceptible snail intermediate hosts for domestic and occupational activities as about 52% of respondents admitted going to the stream/river. Other factors the study revealed to aid the prevalence of schistosomiasis in the communities is lack of political will and commitment to effective schistosomiasis control and eradication by the government. There was also evidence of community involvement and participation in schistosomiasis control in only one of the four communities studied. To eliminate schistosomiasis in the communities, efforts need to be made and sustained by the government at all levels to ensure increased political will with more community involvement and participation to achieve effective schistosomiasis control.